A comprehensive review of pilot ignited high pressure direct injection natural gas engines: Factors affecting combustion, emissions and performance. (March 2020) - Li, Menghan; Wu, Hanming; Zhang, Tiechen; Shen, Boxiong; Zhang, Qiang; Li, Zhenguo
Abstract: With the increasing concern on environmental pollution originated from diesel engines, natural gas, which is widely accepted as a promising alternative fuel for diesel owing to its wide availability and low emissions, has brought into focus. Spark ignition natural gas engines are the most widely used type of natural gas engines. Nevertheless, the thermal efficiency and power output of this type of engines are lower than equivalent diesel engines while HC emissions are relatively higher. It is generally agreed that the drawback of the lower thermal efficiency can be mitigated by using diesel as the pilot fuel instead of using spark plug, however, if natural gas is premixed with air before introduced into the cylinder, the flaw of higher HC emissions still exists. Pilot ignited high pressure direct injection natural gas engines are capable of reaching thermal efficiency equivalent to diesel engines and maintain all the advantages in emissions, thus, have been become a research hotspot. In this paper, the effects of injection parameters (including injection timing, injection pressure and injection interval between pilot diesel and natural gas) on combustion, emissions and performance are presented based on the related published documents. Furthermore, the adaptable load range, the emission reducing effects and the corresponding drawbacks are discussed for different injection strategies. Finally, the effects of injector design and gaseous fuel composition are collected and critically analyzed. Highlights: The effects of injection parameters on combustion, emissions and performance are summarized. The scheme and features of different injection strategies are outlined. The evaluation of injector design and effects of nozzle parameters are analyzed. The engine performance with different gaseous fuel compositions are reviewed.